Metastatic signet-ring cell cancer of the bladder responding to chemotherapy with capecitabine: case report and review of literature - Michels, Jorg; Barbour, Sean; Cavers, Douglas; Chi, Kim N. (Canadian Urological Association Journal, 2013)
Signet-ring cell cancers deriving from the bladder are rare entities and usually present with advanced incurable disease and associated poor outlook. No standard effective chemotherapeutic option has been described largely due to the rarity of this malignancy. We report a case of a patient with metastatic bladder cancer, signet-ring cell variant. The patient progressed rapidly on standard first-line bladder cancer chemotherapy with gemcitabine and carboplatin. He responded well to second-line capecitabine with a clinically meaningful progression-free survival.